The Influence of Brand Awareness, Brand Image, and Product Quality on Repurchase Intention of Fast Fashion Products: Pengaruh Brand Awareness, Brand Image, dan Kualitas Produk Terhadap Repurchase Intention Produk Fast Fashion - Almirah, Olga Violyta; Indayani, Lilik (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the effect of brand awareness, brand image, and product quality on repurchase intention partially or simultaneously. This research is a type of quantitative research with hypothesis testing. The sample used in this study were 100 customers of Zara Sidoarjo city. The analytical tool used is multiple linear regression using the SPSS (Statistical Program for Social Science) for windows program. This primary data was obtained from a questionnaire whose measurement was using a Likert scale. And the data is valid and reliable. The results of the study prove that brand awareness, brand image, product quality partially affect repurchase intention and brand awareness, brand image, and product quality simultaneously affect repurchase intention.